If the circle has a center at (-5,-12) and passes through the origin, then the radius is:
![r=√((-5-0)^2+(-12+0)^2)=13](https://img.qammunity.org/2023/formulas/mathematics/college/9z9tcflh9sh53x43k40m6ilc8zmsy7yw2v.png)
Now, the general formula of a circle is given by:
![(x-h)^2+(y-k)^2=r^2](https://img.qammunity.org/2023/formulas/mathematics/college/5s77z5lwu6jnvb5vkwanu2jvhq5sh1qkc3.png)
Where the circle is (h,k).
Then, we can replace using the values that we know:
![\begin{gathered} (x-(-5))^2+(y-(-12))^2=13^2 \\ (x+5)+(y+12)^2=169 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mwr53y0shmlslbvjawkjqi0pwneva5m3gs.png)
Hence, the correct answer is option C